Personnel Management According to the Four Brahmavihāra Principles in Educational Institutions: Personnel Management According to the Four Brahmavihāra Principles in Educational Institutions - Sangwut, Nittya; Dongponrang , Suthilak; Sanguankhruea, Kotchaphat (RATANABUTH JOURNAL, 2025)
Concepts about personnel management It is a social process that relies on groups of people working together. To achieve the organization’s goals the main aim is to make the work achieve the organization’s objectives efficiently and always evolving and there are many theories about personnel management. In this article, Maslow’s theory of the hierarchy of needs has been presented. There are 5 stages: 1) Physical needs, such as the four essential needs. sexual desire, etc. 2) Needs for safety and security, such as being protected taking care when sick and stable work 3) Social needs participation and acceptance by society 4) The need for respect from others. and the need for self-acceptance and esteem. 5) The need for maximum self-achievement It is the need to develop oneself according to one’s highest potential. That is, when the final destination is reached, there will be further goals according to one’s potential. As for personnel management according to the 4 Brahmavihāra principles in educational institutions, educational institution administrators can apply the 4 Brahmavihāra principles, namely kindness, compassion, mutita, and upekkha, namely: 1) Applying kindness in personnel management. 2) Adopting kindness in personnel management, 3) Adopting mudita in personnel management, and 4) Adopting equanimity in personnel management, such as conflict management. You should listen to all sides objectively. When there is a problem or conflict executives who use equanimity are able to carefully consider the facts. Don’t be attached to personal feelings. and make fair decisions therefore, school administrators who are able to control their emotions and make fair decisions will gain the respect and confidence of personnel and can lead educational institutions to success.